Pemahaman Hadis Tentang Mencukur Alis (studi Analisis Hadis Dalam Kitab Sunan An-Nasa’i) - Akbar, Insan (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
This study aims to discuss eyebrow embroidery in the perspective of hadith. This research is a qualitative type by applying literature study. The results and discussion of this study include an overview of eyebrow embroidery, a review of the hadith about namaṣ (shaving or plucking the eyebrows) and the relevance of the hadiths about shaving the eyebrows in relation to today's concrete reality. This study concluded that shaving the eyebrow hair is haram if it is completely shaved or removed, eyebrow embroidery or eyebrow tattoo because it can remove the original structure of the eyebrows and have a bad impact on health. This is what is said in the hadith to change Allah's creation. This research is expected to provide benefits for a wide audience of Muslims, especially women. It is admitted that this research has limitations in presenting the hadith related to Sulam Alis. This study recommends that further research be conducted on the hadith about Sulam Alis which has a correlation with contemporary concepts.